Interactions between glacial activity, dust-borne iron speciation, diatom productivity, and the biological pump - Shoenfelt, Elizabeth Marie (2019)
Dust-borne iron plays an important role in modulating climate. Iron is a necessary micronutrient, crucial to growth of phytoplankton that fix atmospheric carbon dioxide into organic carbon. Bioavailable iron is relatively scarce in the oxygenated ocean due to the low solubility of oxidized iron, and it limits primary production in many ocean regions. Increased dust-borne iron reaching iron-limited regions is associated with lower atmospheric carbon dioxide, due to more complete utilization of new nitrogen (the biological pump). Since iron solubility in the ocean is low, most iron is in the solid phase, including particles and colloids from dust and insoluble iron oxyhydroxide minerals that precipitate when there is high dissolved iron not chelated by organic ligands. The chemical form (speciation) of iron greatly impacts its solubility, yet the mechanisms of solid-phase iron utilization by diatoms and the impact of solid-phase iron speciation on dust-borne iron bioavailability are not well known. Glacial activity has been associated with highly soluble minerals, but the impact of glacial activity on bioavailable iron supply has not previously been quantified. In this dissertation, I investigate the role of solid-phase dust-borne iron speciation on its bioavailability to iron-efficient diatoms, and its possible role in modulating climate through the efficiency of the biological pump in the Southern Ocean. In Chapter 1, I show that primary iron(II) silicates mobilized from bedrock through glacial physical weathering are more bioavailable than chemical weathering products such as iron(III)-rich iron oxyhydroxides and secondary clay minerals. In Chapter 2, I show that diatoms use solid-phase iron more efficiently when surface contact between the cell and particle is allowed, suggesting a mechanism of solid-phase iron utilization in addition to bulk solubility. In Chapter 3, I show that glacial activity increases the relative bioavailability of dust-borne iron reaching the Southern Ocean, by increasing the iron(II) ...